Deteminants affecting the usage of halal cosmetics among millennial in Melaka / Anis Adilah Aminudin - Aminudin, Anis Adilah (Faculty of Business and Management, 2020)
In Malaysia, the demand of Halal cosmetics and personal care products are growing rapidly. However, there are only few Halal cosmetics brand with Halal certification in the Malaysia cosmetics market. Therefore, this study is seeks to examine the determinants affecting the usage of Halal cosmetics among millennial in Melaka. The independent variable that been examined in this study are awareness and understanding, perceived attributes of innovation, product characteristics and social influence. The data were collected from 216 respondents by using convenience sampling. The findings of this project paper indicate that two independent variables which are product characteristic and social influence have significant relationship with the usage of Halal cosmetics among millennial in Melaka. The outcomes can be useful to several parties such as government, cosmetics company, the future researcher to ensure that sector of Halal cosmetics and personal care can be expand successfully in Malaysia.